Tìm hiểu đôi nét về văn hóa ẩm thực của người Việt qua tục ngữ - Hương, Nguyễn Việt (VNU Journal of Science: Social Sciences and Humanities, 1999)
The author has discovered vSonie |)rol)l(‘ms of Vietnamese gastronomic culture that have been reflocted in proverbs: The im]) 0 i l a n t role of e a tin g and drinking in the life; eating and drinking knowledges; eating and drinking style... The author also has mentioned on the conception, the thinking and the way of troatm enl of Vietnamese to assort th at gastronomic culture is one of the eleMiionls making the feature of Violnameso culture